The IS6 family, a clinically important group of insertion sequences including IS26 - Varani, Alessandro [UNESP]; He, Susu; Siguier, Patricia; Ross, Karen; Chandler, Michael (Bmc, 2021)
The IS6 family of bacterial and archaeal insertion sequences, first identified in the early 1980s, has proved to be instrumental in the rearrangement and spread of multiple antibiotic resistance. Two IS, IS26 (found in many enterobacterial clinical isolates as components of both chromosome and plasmids) and IS257 (identified in the plasmids and chromosomes of gram-positive bacteria), have received particular attention for their clinical impact. Although few biochemical data are available concerning the transposition mechanism of these elements, genetic studies have provided some interesting observations suggesting that members of the family might transpose using an unexpected mechanism. In this review, we present an overview of the family, the distribution and phylogenetic relationships of its members, their impact on their host genomes and analyse available data concerning the particular transposition pathways they may use. We also provide a mechanistic model that explains the recent observations on one of the IS6 family transposition pathways: targeted cointegrate formation between replicons.
Keywords: Insertion sequence; Phylogeny; Genome impact; Transposition mechanisms; Clinical importance; Antibiotic resistance